Political Economy of Regional Integration: Europe, East/Southeast Asia, Latin America Compared - Riza Noer Arfani (Journal of World Trade Studies, 2010)
Despite resilient trends towards globalized economy, the post-cold war landscape of international political economic relations has been characterized by wide-ranging regional arrangements. The process predominantly aims at easing trans-border management in the frame of liberalizing economic (in terms mainly of trade) relations. The regionalization processes modeled after that of the European one highlight the development of regional integration elsewhere around the globe. East/Southeast Asian and Latin American regional arrangements in particular are among major examples. The establishment of AFTA (ASEAN Free Trade Area) covering 10 (ten) Southeast Asian countries which recurrently to be engaged with their East Asian neighboring partners (the so-called ASEAN+3) and MERCOSUR (Mercado Comun del Sur/the Common Market of the South) consisting of 4 (four) southernmost countries of South American continent is the milestone to further regional economic integration in each respective area.